Mixed natural arylolefin-quinolines platinum(II) complexes: Synthesis, structurual characterization and in vitro cytotoxicity studies - 3 (My University, 2018)
Mixed natural arylolefin-quinolines platinum(II) complexes: Synthesis, structurual characterization and in vitro cytotoxicity studies
Keywords: Arylolefin